2021 Guideline for the Management of COPD Exacerbations: Emergency Medicine Association of Turkey (EMAT) / Turkish Thoracic Society (TTS) Clinical Practice Guideline Task Force - AKOĞLU, HALDUN (WOLTERS KLUWER MEDKNOW PUBLICATIONS, 2021)
Chronic obstructive pulmonary disease (COPD) is an important public health problem that manifests with exacerbations and causes serious mortality and morbidity in both developed and developing countries. COPD exacerbations usually present to emergency departments, where these patients are diagnosed and treated. Therefore, the Emergency Medicine Association of Turkey and the Turkish Thoracic Society jointly wanted to implement a guideline that evaluates the management of COPD exacerbations according to the current literature and provides evidence-based recommendations. In the management of COPD exacerbations, we aim to support the decision-making process of clinicians dealing with these patients in the emergency setting.
Keywords: Chronic obstructive pulmonary disease; dyspnea; emergency medicine; practice guideline (MeSH database); HOSPITAL ADMISSION